COMPARATIVE STUDY ON MONGOLIAN LEADERS’ CHARACTERISTICS: A POINT OF VIEW FROM THE FOLLOWERS - Batdelger.N,; Sarantuya.J,; Dashzevge.T, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
We surveyed the Checklist of Admired Leaders (Kouzes & Posner, 2007), ideal format, selecting seven out of the 20 most admired characteristics from 685 Ulaanbaatar residents. Among the most important ideal leader characteristics of UB residents were Broad-minded (61), Competent (58%), Forward-looking (49%), Cooperative (49%), Fair-minded (42%). Kouzes and Posner’s result has been intensively selecting the top 4, and when comparing with the results of our survey the response was widely distributed, even the last characteristics was chosen by 20% of respondents. Also, there are only 2 characteristics which was selected by over 50% of respondents. Age accounted for the differences on Broad-minded, Cooperative, Imaginative, Ambitious and Independent.